Regione “Test” - Gasparini, Roberto; Panatto, Donatella; Dirodi, Bruna; Prato, Rosa; Amunni, Gianni; Turello, Valter; Sudano, Luigi; Cristoforoni, Paolo; Boccalini, Sara; Bonanni, Paolo (Farmeconomia. Health economics and therapeutic pathways, 2012)
In “Test” region 75% of women (aged 24-64) are screened regularly, meaning every 3 years. A cost-effectiveness analysis shows that, considering regional tariffs, the multiple cohort (12-year-old + 25-year-old women) vaccination strategy with a 50% coverage, even if the coverage is much lower than 90%, could prevent 8 cases of cervicocarcinoma and 4 related deaths more than the vaccination of only 12-year-old girls, and thus proves to be cost-effective (8,721 €/QALY).